BASIS KEKUASAAN MASYARAKAT PESISIR DI KAMPUNG NELAYAN SUKU BAJO KELURAHAN PETOAHA KECAMATAN NAMBO TAHUN 2021 - Prayogi jamaluddin calgovsmuis; Eka Suaib; Rahman Tandi (Jurnal Local Politic And Government Issues (Calgovs), 2022)
The objective of this research is to find out the power base of the coastal community in the fishing village of the Bajo tribe, Petoaha Village, Nambo District. The research method used is a type of qualitative research with a descriptive approach. The informants in the research are people who really understand the power base of the coastal community in the fishermen village of the Bajo tribe, Petoaha village, Nambo district. The data analysis techniques used in this study consist of: data reduction, data presentation, and drawing conclusions.Attempts to understand power usually distinguish between different types of power. French and Raven (1959) created a taxonomy to classify various types of power according to their source. This taxonomy has four different types of power, namely: coercive power, expert power, legitimate power, and reward power. Based on the results of research and discussion of the power base of coastal communities in the petoaha sub-district, the fishing village of the Bajo tribe, I can conclude that the people there tend to choose leaders based on the expertise they have such as having served before, proficient in speaking and trustworthy when there are assignments. . So they choose based on the power of expertise.